Influence of process parameters on solidification length of twin-belt continuous casting. (April 2018) - Penumakala, Pavan Kumar; Nallathambi, Ashok Kumar; Specht, Eckehard; Urlau, Ulrich; Hamilton, Doug; Dykes, Charlie
Highlights: Belt heat flux is estimated using thermal resistance network method. Dam block heat flux is estimated using semi-infinite body assumption. Total solidifcation length is proportional to the casting speed. Under the same casting speed and heat flux, decrease of cross section size decreases the solidification length. Abstract: A temperature based Finite Element Model is developed to estimate the evolution of temperature, shell growth profiles and solidification length of a solidifying ingot in a twin-belt caster. The model is based on the 2-D slice which travels through the caster with time. A transient energy equation is solved with the incorporation of thermal boundary conditions which depends on the position of the slice. The latent heat released during the solidification is incorporated through the effective specific heat method. The convective heat flux due to the belts, and dam blocks inside the caster and from spray cooling outside the caster are applied as boundary conditions. The belt heat flux is estimated by incorporating thermal resistances of the cooling water, the belt, the coating, the interface between belt and ingot, the solidifying shell and the melt. At the interface between belt and ingot, the gap dependent heat transfer is considered which is based on the combined mode of radiation and conduction. The amount of gap is calculated iteratively by considering the thermal contraction of the solidifying ingot. The dam block heat flux is estimated by approximating it as a semi-infinite body. The model is applied to the state of the art industrial twin-belt continuous copper casting. The simulated temperature and shell thickness results are compared with the data measured at the industrial caster. It is found that the travelling slice model predicts comparable results with industrial data for high speed copper casting. The model is extremely useful for industrial engineers to know the design aspects of the twin-belt caster such as final solidification length, belt, dam block and ingot dimensions and casting speed. The effect of the process parameters on temperature evolution and shell growth profiles are analysed in detail. The procees length is proportional to casting speed. When the casting speed and heat flux are constant, decrease of cross section size decreases the solidification length